KAJIAN TERHADAP TAFSIR MAHÂSIN AL-TA’WÎL: MENGENAL PRIBADI PENGARANG DAN MANHAJ TAFSIRNYA - Amirotun Nafisah; Musyaffa Ahmad Rahim (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2023)
This research is a scientific study of the life of a prominent scholar of tafsir in the modern era and his method of interpreting the virtues of tafsir. In it, the researcher discusses the life of Al-Qasimi, his works, his sheikhs, and his writings. The researcher reveals the author's method of interpretation that relies on what is narrated from the Qur'an and Sunnah and the sayings of the prophets. Companions and Followers, and the tendency of his interpretation. The researcher answers this problem with research, analysis, and criticism, showing the positive side of the approach, which is large, and mentioning his observations on Al-Qasimi's approach, which is small. His tafsir contains a lot of science and knowledge, from which everyone who reads and reads it will benefit